ECOPRINT TRAINING AS AN INNOVATION IN INCREASING THE CREATIVITY OF WACHID HASYIM ELEMENTARY SCHOOL STUDENTS IN THE CITY OF SURABAYA - Harya, Gyska Indah; Mardika, Anggita; Sisyawati, Raniasani; Fahruddin, Khabib; Prasetyo, Rachmad Dwi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Art education often receives less attention than other academic fields. Art is an activity that can increase creativity and become a means of self-expression for students. Based on these conditions, students strive to raise awareness of art in elementary school students by holding training on making Batik Ecoprint using Tote Bag media. Ecoprinting is a technique for printing batik motifs using natural materials without chemicals such as leaves, flowers, and plants. Ecoprinting activities are included in art activities because they require creativity in doing so. This training activity is one of the activities of KKN-T Defending the Country of UPN